The Impact of Thematic Worksheet-Assisted Meaningful Learning Implementation on Students' Mathematical Concept Understanding and Metacognitive Skills - Fitriana, Eni; Siswanto, Deny Hadi; Hanama, Akhmad (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2025)
This study aims to examine the impact of meaningful learning implementation assisted by thematic worksheets on students' mathematical concept understanding and metacognitive skills using a quantitative descriptive approach. The research employs a quantitative method with a pre-experimental design, specifically the One Shot Case Study design, and uses simple random sampling for sampling techniques. The study was conducted in class XI of Dirgantara Putra Bangsa Vocational High School in October 2024, with 30 students participating. Data collection was carried out through questionnaires on the implementation of meaningful thematic learning assisted by worksheets, metacognitive skills questionnaires, and tests on mathematical concept understanding. The results of the study indicate that: (1) Student responses to meaningful learning assisted by thematic worksheets reached 74.62%, categorized as good; (2) The implementation of meaningful learning assisted by thematic worksheets influenced students' mathematical concept understanding by 88.1%; (3) The implementation also impacted students' metacognitive skills with a contribution of 18.9%. These findings suggest that integrating thematic worksheets into meaningful learning enhances both cognitive and metacognitive outcomes. Future research should consider using more relevant or contemporary themes and exploring broader applications across subjects.